BlockCV: An r package for generating spatially or environmentally separated folds for k‐fold cross‐validation of species distribution models. Issue 2 (8th November 2018) - Valavi, Roozbeh; Elith, Jane; Lahoz‐Monfort, José J.; Guillera‐Arroita, Gurutzeta
Abstract: When applied to structured data, conventional random cross‐validation techniques can lead to underestimation of prediction error, and may result in inappropriate model selection. We present the r package block CV, a new toolbox for cross‐validation of species distribution modelling. Although it has been developed with species distribution modelling in mind, it can be used for any spatial modelling. The package can generate spatially or environmentally separated folds. It includes tools to measure spatial autocorrelation ranges in candidate covariates, providing the user with insights into the spatial structure in these data. It also offers interactive graphical capabilities for creating spatial blocks and exploring data folds. Package block CV enables modellers to more easily implement a range of evaluation approaches. It will help the modelling community learn more about the impacts of evaluation approaches on our understanding of predictive performance of species distribution models. Foreign Language Abstract: هنگامی که روش اعتبارسنجی متقاطع بر روی داده‌های دارای ساختار (مکانی٬ محیطی …) اعمال می‌شود٬ می‌تواند منجر به تخمین نادرست خطای پیشبینی و در نتیجه اشتباه در انتخاب مدل‌ها شود. در اینجا کتابخانه blockCV در نرم‌افزار برنامه‌نویسی R را بعنوان یک ابزار جدید برای اعتبارسنجی متقاطع مدل‌های توزیع گونه‌ها ارائه می‌دهیم. گرچه این کتابخانه با ایده‌ی مدلسازی توزیع گونه‌ها توسعه داده شده است اما می‌تواند برای انواع مدلسازی‌های مکانی نیز مورد استفاده قرار گیرد. این کتابخانه توانایی ساخت زیرمجموعه‌های مجزای مکانی و محیطی از داده‌ها را دارد و همچنین شامل ابزاری برای اندازه‌گیری دامنه تاثیر خودهمبستگی مکانی در متغیرهای پیشبینی‌کننده می‌باشد که به کاربر دیدگاه بهتری از ساختار مکانی این داده‌ها را می‌دهد. این کتابخانه دارای ابزارهای گرافیکی برای بررسی و ساخت بلاک‌های مکانی نیز می‌باشد. کتابخانه blockCV مدل‌سازان را قادر می‌سازد که دامنه وسیع‌تری از روش‌های اعتبارسنجی را بکار گیرند و همچنین درباره تاثیرات روش‌های مختلف اعتبارسنجی بر درک بهتر ما از قدرت پیشبینی مدل‌های توزیع گونه‌ها کمک می‌کند.